Response by Endodontists to the SARS-CoV-2 (COVID−19) Pandemic: An International Survey - Galicia, Johnah C.; Mungia, Rahma; Taverna, Melanie V.; Mendoza, Marissa J.; Estrela, Carlos; Gaudin, Alexis; Zhang, Chengfei; Vaughn, B. Aaron; Khan, Asma A. (Frontiers in Dental Medicine, 2021)
As SARS-CoV2 continues to wreak havoc, health care workers are on the front lines to protect our communities. Dentists, particularly endodontists who manage dental emergencies, are engaged in high risk procedures that necessitate the modification of their treatment strategies in order to protect themselves, their staff and their patients from exposure to SARS-CoV2. This study gathered international data from 448 endodontists to describe their awareness, their clinical care modifications, their strategies for re-opening and their reflection on the effects of the pandemic on their lives. Most endodontic practitioners (78%, n=350) provided but limited their treatments to emergency care during the government-mandated shutdowns. They agreed with their local government’s actions more than that of the national government, screened their patients for symptoms prior to treatment and changed their clinical care protocol to mitigate the spread of the virus. The pandemic has impacted their income, their ability to retain staff, and their financial and personal outlook in life.